2014
DOI: 10.1016/j.jcp.2014.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Exponential versus IMEX high-order time integrators for thermal convection in rotating spherical shells

Abstract: We assess the accuracy and efficiency of several exponential time integration methods coupled to a spectral discretization of the three-dimensional Boussinesq thermal convection equations in rotating spherical shells. Exponential methods are compared to implicitexplicit (IMEX) multi-step methods already studied previously in [1]. The results of a wide range of numerical simulations highlight the superior accuracy of exponential methods for a given time step, especially when employed with large time steps and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Similar problems occur in time evolution codes in spheres or spherical shells when the nonlinear terms are truncated. This was noticed in [52] and by the authors in their implementations of codes in the case of spherical shells [34,35,37,38]. In some cases the numerical instability shows up only after long time integrations.…”
Section: Spurious Eigenvaluesmentioning
confidence: 76%
See 2 more Smart Citations
“…Similar problems occur in time evolution codes in spheres or spherical shells when the nonlinear terms are truncated. This was noticed in [52] and by the authors in their implementations of codes in the case of spherical shells [34,35,37,38]. In some cases the numerical instability shows up only after long time integrations.…”
Section: Spurious Eigenvaluesmentioning
confidence: 76%
“…These methods have been used successfully in the case of spherical shells [33][34][35]37,38]. They are very efficient due to the possibility of using optimized matrix-matrix products to evaluate the action by the operators in order to compute the nonlinear terms in the time evolution of the full non-linear equations.…”
Section: Radial Discretizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it turns out to be challenging to find a computationally efficient formulation including the Coriolis effect, which allows large time steps. An application of exponential integrators in the context of atmospheric simulations can be found, for example, in the work of Garcia et al Here, significant improvements in accuracy were observed; however, performance issues under realistic test conditions were found to be a severe issue.…”
Section: Introductionmentioning
confidence: 98%
“…Notice that a centered finite difference could be also considered, although at the price of doubling the evaluations of R(f ); this solution has been considered in [GBNS14]. A second consequence is that a stopping criterion must be provided: a large number of iterations results in an accurate approximation of φ (∆t J n R ), but also leads to a higher computational cost.…”
Section: Upwind Discretization Of the Vlasov Equationmentioning
confidence: 99%